State-sponsored Populism and the Rise of Populist Governance: The Case of Montenegro. Issue 4 (4th July 2017) - Džankić, Jelena; Keil, Soeren
Abstract: Ever since it became independent in 2006, Montenegro has steadily progressed in its ambition to accede to the European Union. Even so, a new form of populism, dominated by neither a far-right nor a far-left discourse, but controlled by leading political elites in the country's government has developed in Montenegro. This form of populism is not a mechanism of ensuring the dominance of the Democratic Party of Socialists (Demokratska Partija Socijalista Crne Gore, DPS) in Montenegro per se. Instead it is used as a tool to support and enhance other mechanisms that the party utilizes in order to stay in power and remain the dominant force in the country. Hence, we can observe the growth of a new kind of populism, a state-sponsored populist discourse that is very different from populism as understood in Western Europe. What we find in Montenegro is a government that uses populist language and messages to support a clientelistic state system.